2004
DOI: 10.1002/pi.1745
|View full text |Cite
|
Sign up to set email alerts
|

Dependency of the shape memory properties of a polyurethane upon thermomechanical cyclic conditions

Abstract: The relationship between the shape memory properties and thermomechanical cyclic conditions was investigated with a type of shape memory polyurethane (SMPU). The thermal and dynamic mechanical properties of the polyurethane were examined by using differential scanning calorimetry (DSC) and dynamic mechanical analysis (DMA). It was found that the SMPU exhibited good shape memory effects (SMEs) at deformation temperatures ranging from Tg to Tg + 25 °C. The strain recovery ratios increased with the increase of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
120
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 154 publications
(129 citation statements)
references
References 21 publications
6
120
0
Order By: Relevance
“…about 83.1-84.5% at T g -)10°C and 96.5-97.4% at T g -)20°C, are still higher than that of polyurethane SMPs (i.e. about 77% at T g -)10°C and 95% at T g -)20°C) [47] suggesting a less chain mobility of our polymer network comparing at the same fixing temperature below their T g above.…”
Section: Effect Of Ba-a Contents On Shape Fixity Ofmentioning
confidence: 89%
“…about 83.1-84.5% at T g -)10°C and 96.5-97.4% at T g -)20°C, are still higher than that of polyurethane SMPs (i.e. about 77% at T g -)10°C and 95% at T g -)20°C) [47] suggesting a less chain mobility of our polymer network comparing at the same fixing temperature below their T g above.…”
Section: Effect Of Ba-a Contents On Shape Fixity Ofmentioning
confidence: 89%
“…Compared with shape memory metallic alloys and shape memory ceramics, SMPs possess the advantages of light weight, low cost, good processability, high shape deformability and recoverability, and tailored switch temperature [1][2][3][4][5][6][7][8][9][10]. Since the 1990s, SMPs have been increasingly developed and widely applied in smart textiles and apparels [11,12], intelligent medical devices [13][14][15], and self-deployable structures in spacecrafts [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Influence of deformation temperature on structural variation and shape-memory effect of a thermoplastic semi-crystalline multiblock copolymer The deformation temperature (T deform ) has significant effects on deformation behaviors of semi-crystalline polymers on the microscopic and macroscopic scale [9,10], with structural variations during the deformation playing a dominant role in determining their mechanical properties [11,12]. It also has been reported that T deform can affect the SME of semicrystalline MBCs, i.e., if the samples are deformed at a temperature lower than the thermal transition temperature (T trans ) of switching domains, reduction in fixity ratio (R f ) and switching temperature (T sw ) can be observed as well as a higher maximum stress (!…”
mentioning
confidence: 99%